Optimizing City Diplomacy Indonesia for Economic Development Through E-government Implementation - Putri, Sylvia Octa (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
This research wants to identify the implementation of e-government conducted by the city government in Indonesia that could synergize and support city diplomacy activity in boosting city economic development. The research method was qualitative methods, with data collection techniques through literature studies. The results showed that the implementation of E-government in several cities in Indonesia are still focused on improving the quality of public services, using the use of information technology through the pattern of Government to Citizen (G2C), Government to Business (G2B), Government to Government (G2G). The orientation of data and information distribution is still focused on the local population. The use of multilingual or foreign language options in accessing information is still less optimal. Various fields that can boost the city’s development, such as investment, trade, and tourism with a focus on overseas audiences, are informed well but the data or information presented is not integrated into one portal. There are several cities that are considered doing city diplomacy very well, by combining the e-government implementation and city diplomacy will greatly improve and accelerate the city’s economic development, and the city could be becoming an important player at the global level.